2021
DOI: 10.1021/acsomega.1c01882
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Coated Au Nanoparticle Toxicity Is Preferentially Triggered Via Mitochondrial Nitric Oxide/Reactive Oxygen Species in Human Liver Cancer (HepG2) Cells

Abstract: Reactive nitrogen species (RNS) that are formed from the reaction of versatile nitric oxide (NO) with reactive oxygen species (ROS) have been less explored in potential cancer therapy. This may be partly due to the fewer available agents that could induce NO in cells. Here, we report platinum-coated gold nanoparticles (Pt-coated Au NPs; 27 ± 20 nm) as a strong inducer of NO (assessed by live-cell imaging under NO-specific DAR-1 probe labeling and indirectly using a Griess reagent) in human liver carcinoma (Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
2
3
0
Order By: Relevance
“…A substantial depletion of GSH content in Pt-treated cells after 24 and 48 h reached 28 nM/µg protein and 21 nM/µg protein, respectively, with reference to the untreated control cells (39 nM/µg protein for 24 h and 31 nM/µg protein for 48 h). A decrease in the GSH level after pro-oxidative Pt-containing NPs was also observed in previously published research with different cell lines [ 18 , 19 , 20 ]. It was concluded that GSH depletion is highly dependent on the size of PtNPs, wherein usually smaller nanoparticles (<20 nm) were able to induce a more significant reduction of GSH level.…”
Section: Resultssupporting
confidence: 81%
“…A substantial depletion of GSH content in Pt-treated cells after 24 and 48 h reached 28 nM/µg protein and 21 nM/µg protein, respectively, with reference to the untreated control cells (39 nM/µg protein for 24 h and 31 nM/µg protein for 48 h). A decrease in the GSH level after pro-oxidative Pt-containing NPs was also observed in previously published research with different cell lines [ 18 , 19 , 20 ]. It was concluded that GSH depletion is highly dependent on the size of PtNPs, wherein usually smaller nanoparticles (<20 nm) were able to induce a more significant reduction of GSH level.…”
Section: Resultssupporting
confidence: 81%
“…Significant decrease in ceramide content in HepG2 cells treated with 5 and 10 µM BSO correlated with an increase in HepG2 cell proliferative potency. These findings are in full accord with Jin et al [46] and Akhtar et al [47], who reported that HepG2 cell viability was unscathed following treatment with BSO concentrations up to 200 µM. HepG2 cells survived treatment with one mM treatment with BSO for 20 h [48].…”
Section: Discussionsupporting
confidence: 88%
“…glutathione depletion and oxidative stress elicited Hela [ 50 ] and methocelioma [ 51 ] cell death. Liver and hepatoma cells renowned for their low nSMase2 content [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] and Figure 3 differ, as high BSO concentrations translated in extremely low glutathione content and tremendous increase in ROS accumulation led to a remarkable increase in HepG2 cell proliferative potential [ 46 , 47 , 48 ] and Figure 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence from in vitro and in vivo studies supported that NM inhalation exposure can induce excessive production of reactive oxygen (ROS, including super oxides, superoxide radicals, hydroxyl radicals and hydrogen peroxide) and reactive nitrogen species (RNS, including peroxynitrite anion and nitric oxide) [ 50 , 51 ]. The ROS could react with the chain polyunsaturated fatty acids in the membrane to trigger the process of lipid peroxidation, resulting in the release of reactive, toxic aldehydes, including MDA, HNE and aldehydes C6-C12 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%